PENGARUH KEPEMIMPINAN AUTENTIK DAN WORK ENGAGEMENT TERHADAP PSYCHOLOGICAL CAPITAL PEGAWAI KANTOR PENCARIAN DAN PERTOLONGAN KELAS A MAKASSAR - Wendy Hogianto; Idrus Stambul; Orfyanny Syahreffy Themba (Prodi Manajemen, 2024)
The influence of authentic leadership and work engagement on psychological. This research was conducted with the main objective of knowing and analyzing and making scientific contributions related to authentic leadership and work engagement to psychological capital in the Makassar class A search and rescue office. This study had a population of 119 with 49 total samples. This study used incidental sampling techniques through the application of saturated samples. This study used several statistical tests, including: validity, reliability, normality test, multicollinearity test, heterokedasticity test, t test, F test, multiple linear regression analysis test, and determination coefficient test. The research found that authentic leadership had a positive but not significant influence on psychological capital. This is because the calculated t-test value of authentic leadership is smaller than the table t, which is 1.788 < 2.012 with a significance of 0.080. Work engagement has a positive and significant influence on psychological capital. In other words, the study found the calculated t value of work engagement was greater than the table t of 5.219 > 2.012 with a significance of 0.000.